Design and implementation of a wireless sensing data exchange system - Sun, Xiaolei (2019)
Wireless sensor networks constitute a powerful technology particularly suitable for environmental monitoring. This report describes in designing and implemented a sensing and data exchange network. Firstly, research has been conducted on relevant fields on wireless technologies, communication networks. Secondly, lists of material are chosen to meet the requirements of the system. After that, description and demo of how to transfer data using Zigbee are covered. Lastly, the report followed by further development which also mentioned with literal review. The results obtained from this project shows that successful data packet transmission is achievable.